Conceptualisation of Hotel Guest Experience Assessment Process and Electronic Words of Mouth - Chao, Han; Rashid, Basri (Journal of Indonesian Tourism and Development Studies, 2020)
The success of a hotel depends on the guests' interpretation and reviews of their visit experience. Guests who perceived their visit experience as worthiness and satisfactory would circulate their experience to their acquaintances. In today's information based era, their visit experience can be widely circulated through electronic word of mouth (e-wom) such as the social media. This paper aims to construct a research framework to study hotel guests experience responses as the result from their encounters with the hotel's products and services during their stay. Unforgettable encounters would influence the guests' future behaviour, starting with their commitment and eventually translated into reaction in the forms of electronic word of mouth responses. Methodically, an exhaustive review of the literature was carried out to establish a theoretical underpinning of hotel guests experience assessment process and their future responses. Perceived value and satisfaction are deemed as important measurements in the initial stage of the hotel guest visit experience outcomes. In line with the current information technology trends, the guests are expected to use electronic word of mouth to disseminate their visit outcomes. Academically, the study framework reduces the gaps related to the formulation of research constructs for hotel visit experience assessment. It is assertive that this paper would be practically beneficial to hotel operators or relevant stakeholders in order to gain a comprehensive understanding about hotel guests' visit experience responses and their future behaviour, including the electronic word-of-mouth response. Keywords: Commitment, electric word-of-mouth, hotel, perceived value, post visit responses, satisfaction.